Mesas, giras, toques e sambas: intolerância e legitimação dos cultos afro-brasileiros paraibanos - Fonseca, Ivonildes da Silva (2011)
Religious intolerance is a topic that has attracted the attention of researchers especially in relation to african-brazilian religions. In Paraiba, these studies are still incipient and thus this study aimed to identify manifestations of intolerance and reactions that have been engendered in the cities of Joao Pessoa, Sape, Guarabira and Alagoa Grande. To account for the theoretical support of the research came from the symbolic interactionism of weberian concepts and bourdianos, and authors who study the field of african-brazilian religions. The qualitative research made use of the techniques of field observation and interviews in order to favor their own data in the search field and by the agents themselves religious. In this theoretical part were visited twenty-three yards, and selected and contacted twenty-three religious leaders. After interviewing the twenty-three leaders, nine were chosen to interact in the interview technique with depth, resulting sometimes in more than two interviews with the same person. From the thematic readings and field work defined the field of religious african-brazilian religions in Paraiba. Religious intolerance was approached conceptually and empirically allowing the understanding that legitimacy in its social sense is a condition not yet achieved by these religions in spite of legal legitimacy. In search of social acceptance of the construction of legitimacy is a process that is being developed through the development of mechanisms called, from the contribution of concepts berger: cognitive, normative and cognitive-normative.